1991
DOI: 10.1136/thx.46.11.807
|View full text |Cite
|
Sign up to set email alerts
|

Self reported snoring and daytime sleepiness in men aged 35-65 years.

Abstract: Background It has been suggested that snoring alone, without conventional sleep apnoea or hypopnoea, may disrupt sleep and produce substantial daytime hypersomnolence. This study addresses this potential relationship. Method Eight hundred and fifty men, aged 35-65 years, drawn from one general practice were visited at home and asked a range of questions potentially related to sleepiness, snoring, and sleep apnoea; these included inquiries about alcohol and cigarette consumption, nasal stuffiness, shift work, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 20 publications
5
32
0
1
Order By: Relevance
“…The association between snoring and excessive daytime sleepiness has been identified previously in several studies performed in Western countries. 16 factors, and somatic and psychological complaints were associated with sleep problems. Ohida et al reported that unhealthy lifestyle-related factors such as lack of exercise and irregular eating habits, and also poor health status, were associated with short sleep duration and subjectively insufficient sleep.…”
Section: Logistic Regression Analysis Of Excessive Daytime Sleepinessmentioning
confidence: 99%
“…The association between snoring and excessive daytime sleepiness has been identified previously in several studies performed in Western countries. 16 factors, and somatic and psychological complaints were associated with sleep problems. Ohida et al reported that unhealthy lifestyle-related factors such as lack of exercise and irregular eating habits, and also poor health status, were associated with short sleep duration and subjectively insufficient sleep.…”
Section: Logistic Regression Analysis Of Excessive Daytime Sleepinessmentioning
confidence: 99%
“…2.3.3 Body movements Many attempts have been made to define the sleep/wakefulness cycle by measuring movement (Sadeh et al 1989;Vos and Stradling 1991;Webster et al 1982). Whilst these have been fairly successful, there are problems related to the sensitivity of such movement detectors, the part of the body upon which they are placed, and ignorance as to whether all forms of sleep disturbance and fragmentation lead to measurable body movement.…”
Section: Eog Onlymentioning
confidence: 99%
“…Lesser degrees of upper airway narrowing associated with snoring, increased inspiratory efforts and sleep fragmentation, may also result in decreases in daytime alertness [4][5][6]. It has even been suggested that there is a syndrome of increased upper airway resistance, causing increases in inspiratory effort and arousals from sleep, in the absence of either snoring or abnormal conventional sleep staging [7].…”
mentioning
confidence: 99%